2019
DOI: 10.1177/0193945919828061
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Rural Tobacco Use, Smoke-Free Policies, and Tobacco Taxes

Abstract: Tobacco use and exposure to secondhand smoke (SHS) remain leading causes of preventable disease, disability, and mortality in the United States. Rural populations are among those being left behind in the recent declining smoking rates and have become a focus of discussions on tobacco-related disparities. This article describes tobacco-related disparities in rural populations including tobacco use, exposure to SHS, smoke-free policies, and tobacco taxes. Nurses, as social justice and tobacco control policy advo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 49 publications
(68 reference statements)
1
44
1
3
Order By: Relevance
“…We found that a significantly higher percentage of participants from rural areas reported that they had increased tobacco use during this pandemic compared to those from urban areas. Several studies demonstrated that tobacco use is significantly higher among rural inhabitants than those of urban areas [ 26 , 27 ]. However, the reasons behind the increased frequency of tobacco use among rural participants compared to those in urban areas during this pandemic remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that a significantly higher percentage of participants from rural areas reported that they had increased tobacco use during this pandemic compared to those from urban areas. Several studies demonstrated that tobacco use is significantly higher among rural inhabitants than those of urban areas [ 26 , 27 ]. However, the reasons behind the increased frequency of tobacco use among rural participants compared to those in urban areas during this pandemic remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The warnings provide general statements about the health consequences of tobacco use, stating that smoking causes death, lung cancer, stroke, heart disease, respiratory problems, or other problems. The text warnings cover up at least 50% of the front and back of cigarette and bidi packs [ 27 ]. In addition, the Bangladesh government initiated a policy to increase the price and taxes for all kinds of cigarettes and tobacco products, including upward adjustment tax rates [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the higher prevalence at lower age group and lower age at first initiation compared to national data point to the need for enhanced tobacco control policies, such as taxes, smoke-free policies, and regulation of marketing practices. Historically, such policies and practices have not been widely implemented in rural communities [ 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, disparate subpopulations are inherently heterogeneous. Buettner-Schmidt, Miller, and Maack (2019) consider the heterogeneity of the rural population as critically important, and interventions may need to be tailored in rural areas. Similarly, Okoli and Seng (2019) found that different psychiatric diagnoses are associated with tobacco use and recommend tailoring tobacco treatment to the diagnosis as well as the place (rural vs. urban).…”
mentioning
confidence: 99%
“…Nurses have their roots in social justice and are particularly well suited to consider tobacco as a social justice issue. Buettner-Schmidt et al (2019) call on nurses to mobilize to level of the tobacco control “playing field” in both rural and urban areas. Targeting vulnerable groups and tailoring prevention and treatment within these groups, and recognizing the heterogeneity within subpopulations are critically important to promoting social justice.…”
mentioning
confidence: 99%